Diagnostic Tools to Assess Social Media Presence for Marketers of Experiential Products: Exploring the Wine-related Social Media Interactions - David Dean; Sharon Forbes; Valerie Manna (Jurnal Internasional Penelitian Bisnis Terapan, 2020)
The purpose of this paper is to employ available search and analytical tools to explore the type and quality of information that can be derived from large scale social media interactions. Using graphical techniques such as wordclouds, tracking wordclouds over time, and sociograms (including name and chain social networks), a wealth of information can be derived from the candid and public social media statements and interactions that have become a part of everyday life. The first step to turning this vast source of data into usable diagnostic social media marketing information is understanding how to interrogate the social networks. This research offers search strategies and techniques for Twitter, Facebook, and Instagram. This research looks at wine-related social media posts during a one-week period in August 2016 resulting in 1450 posts (tweets) in Twitter, 10,000 posts in Instagram, and 250 posts in a Facebook group. Specific research and marketing strategies and recommendations are directed to those in the wine industry.